Experimental investigations of the performance of a solar air collector with latent heat thermal storage integrated with the solar absorber - Charvát, Pavel; Pech, Ondřej; Hejčík, Jiří (EDP Sciences, 2013)
The paper deals with experimental investigations of the performance of a solar air collector with latent heat thermal storage integrated with the solar absorber. The main purpose of heat storage in solar thermal systems is to store heat when the supply of solar heat exceeds demand and release it when otherwise. A number of heat storage materials can be used for this purpose; the phase change materials among them. Short-term latent heat thermal storage integrated with the solar absorber can stabilize the air temperature at the outlet of the collector on cloudy days when solar radiation intensity incident on a solar collector fluctuates significantly. Two experimental front-and-back pass solar air collectors of the same dimensions have been built for the experimental investigations. One collector had a "conventional" solar absorber made of a metal sheet while the solar absorber of the other collector consisted of containers filled with organic phase change material. The experimental collectors were positioned side by side during the investigations to ensure the same operating conditions (incident solar radiation, outdoor temperature).

The paper deals with experimental investigations of the performance of a solar air collector with latent heat thermal storage integrated with the solar absorber. The main purpose of heat storage in solar thermal systems is to store heat when the supply of solar heat exceeds demand and release it when otherwise. A number of heat storage materials can be used for this purpose; the phase change materials among them. Short-term latent heat thermal storage integrated with the solar absorber can stabilize the air temperature at the outlet of the collector on cloudy days when solar radiation intensity incident on a solar collector fluctuates significantly. Two experimental front-and-back pass solar air collectors of the same dimensions have been built for the experimental investigations. One collector had a "conventional" solar absorber made of a metal sheet while the solar absorber of the other collector consisted of containers filled with organic phase change material. The experimental collectors were positioned side by side during the investigations to ensure the same operating conditions (incident solar radiation, outdoor temperature).
Experimental investigations of the performance of a solar air collector with latent heat thermal storage integrated with the solar absorber
Keywords: Air solar collector; latent heat thermal storage; PCM; Air solar collector; latent heat thermal storage; PCM